Promotion, Turnover, Earnings, and Firm‐Sponsored Training - Owan, Hideo (Journal of Labor Economics, 2004)
I develop a model in which different technological conditions lead to distinct equilibria with different patterns in labor mobility, promotion, earning distribution, and provision of firm‐sponsored training. Key is the asymmetric learning of workers’ characteristics. Because of the information that is conveyed to the market by promotion, firms have incentives to adopt strategic promotion policies, which result in different patterns in the use of internal labor market. The theory explains well the differences between the Japanese and the United States labor markets.